Lethal letters eaudiobook - Adams, Ellery (Books by the Bay Mystery, 2015)
Everyone's got their hands full in Oyster Bay, North Carolina. Aside from two upcoming weddings, there's also the historical society's annual fund-raiser: the Secret Garden Party and Candlelit Ball. Adding to the excitement, Olivia witnesses the discovery of a time capsule in the foundation of a local church. The historical society president hopes to display its contents at their party, but when the items are finally revealed to the public, Olivia notices that one of them has vanished. After a frightening find beneath the pier—the body of Ruthie Holcomb—Olivia is certain that there's a connection between the young woman's death and the missing piece from the time capsule. With the help of her fellow Bayside Book Writers, Olivia sets out to uncover some clues and ensure that a killer has no reason to celebrate . . .